Does sex affect the risk of 30-day all-cause mortality in cardiogenic shock? - Schmitt, Alexander; Schupp, Tobias; Rusnak, Jonas; Ruka, Marinela; Egner-Walter, Sascha; Mashayekhi, Kambis; Tajti, Péter; Ayoub, Mohammed; Behnes, Michael; Akın, Ibrahim; Weidner, Kathrin (International journal of cardiology, 2023)
Background - Mortality rates following cardiogenic shock (CS) have stagnated on an unacceptably high level. Limited data regarding the prognostic value of sex in patients suffering from CS is available. Therefore, this study aims to investigate the prognostic value of sex in patients with CS. - Methods - Consecutive patients with CS of any cause were included from 2019 to 2021. Prognosis of females was compared to males regarding 30-day all-cause mortality. Further risk stratification was performed according to the presence or absence of CS related to acute myocardial infarction (AMI). Kaplan-Meier and multivariable Cox proportional regression analyses were applied for statistics. - Results - From a total of 273 CS patients (AMI-CS: 49%; non-AMI-CS: 51%), 60% were males and 40% females. The risk of 30-day all-cause mortality did not differ among males and females (56% vs. 56%; log rank p = 0.775; HR = 1.046; 95% CI 0.756-1.447; p = 0.785). Even after multivariable adjustment, sex was not associated with prognosis in CS patients (HR = 1.057; 95% CI 0.713-1.564; p = 0.784). Comparable risks of short-term mortality in both sexes were observed irrespective of the presence of AMI-related CS (64.0% vs. 64.6%; log rank p = 0.642; HR = 1.103; 95% CI 0.710-1.713; p = 0.664) and non-AMI-related CS (46.2% vs. 49.2%; log rank p = 0.696; HR = 1.099; 95% CI 0.677-1.783; p = 0.704). - Conclusion - Sex was not associated with the risk of 30-day all-cause mortality in CS patients irrespective of CS etiology. (clinicaltrials.gov identifier: NCT05575856)